Systemic Violence and Female Subjection in William Vega’s 'The Towrope' - Montes Garcés, Elizabeth (Comunicación y Género [Communication and Gender], 2019)
William Vega’s La Sirga [The Towrope] (2012) depicts the story of Alicia, a girl who flees from her hometown when members of a paramilitary group kill her parents. Drawing on Slavoj Žižek’s concepts of systemic violence and Judith Butler’s theories on subjection and power, this article will demonstrate that in the film the male characters’ eyes act as the surveying gaze that attempts to construct Alicia as an obedient subject who shouldn’t deviate from the traditional social role assigned to Colombian women.
Keywords: Systemic Violence; Female Subjection; William Vega’s The Towrope; Colombia